Elite clientelism in Nigeria: The role of parties in weakening legislator-voter ties. (September 2022) - Demarest, Leila
Political parties in Africa and other developing countries are known to forge clientelist rather than programmatic ties to voters. Yet this does not mean that parties reward strong legislator-voter ties. In this paper, I argue for the case of Nigeria that lawmakers seeking to advance their political careers are incentivized to direct public resources to party members and senior party elites rather than serve their constituents in general. I draw on interviews with 8th National Assembly (2015–2019) lawmakers as well as quantitative data on MP re-election, targeted bills and motions, and the use of constituency development funds to demonstrate the predominance of narrow clientelism in Nigeria. I also place the Nigerian case in comparative perspective to argue that the extent to which legislators devote attention to constituents is likely to exist on a continuum, with the causes and consequences of this variation requiring further attention from scholars.